2024
DOI: 10.3390/molecules29071598
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitroatenolol: First Synthesis, Chiral Resolution and Enantiomers’ Absolute Configuration

Rosa Sparaco,
Pierfrancesco Cinque,
Antonia Scognamiglio
et al.

Abstract: 4-Nitro and 7-nitro propranolol have been recently synthesized and characterized by us. (±)-4-NO2-propranolol has been shown to act as a selective antagonist of 6-nitrodopamine (6-ND) receptors in the right atrium of rats. As part of our follow-up to this study, herein, we describe the first synthesis of (±)-3-nitroatenolol as a probe to evaluate the potential nitration of atenolol by endothelium. Chiral chromatography was used to produce pure enantiomers. By using Riguera’s method, which is based on the sign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The absolute configuration of 1 was assigned as (5R,1′R) by a single-crystal X-ray diffraction experiment using Cu-Kα radiation [16] were observed in the same CDCl3 solvent, which suggested that 2 could be a 5-epimer of 1 (Table 1). The absolute configuration of the secondary hydroxylated carbon (C-1′) was determined using a modified Mosher's method [17][18][19][20]. The chemical shifts for H-2′, H-4, and H-7 of 1a and 1b were measured as δH 1.49, 4.94, 2.38 for 1a, and δH 1.44, 4.96, 2.49 for 1b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absolute configuration of 1 was assigned as (5R,1′R) by a single-crystal X-ray diffraction experiment using Cu-Kα radiation [16] were observed in the same CDCl3 solvent, which suggested that 2 could be a 5-epimer of 1 (Table 1). The absolute configuration of the secondary hydroxylated carbon (C-1′) was determined using a modified Mosher's method [17][18][19][20]. The chemical shifts for H-2′, H-4, and H-7 of 1a and 1b were measured as δH 1.49, 4.94, 2.38 for 1a, and δH 1.44, 4.96, 2.49 for 1b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2 shared the same planar structure as 1 and was further identified by 2D NMR spectra, including 1 1). The absolute configuration of the secondary hydroxylated carbon (C-1′) wa determined using a modified Mosher's method [17][18][19][20]. The chemical shifts for H-2′, H-4 and H-7 of 1a and 1b were measured as δH 1.49, 4.94, 2.38 for 1a, and δH 1.44, 4.96, 2.49 fo 1b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation